2013
DOI: 10.1177/03946320130260s102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Karyotype of Expanded Human Adipose-Derived Stem Cells for Bone Reconstruction of the Maxillo-Facial Region

Abstract: Mesenchymal stem cells (MSC) and adipose-derived stem cells (ASC) were recently proposed for bone maxillofacial reconstruction in association with biomaterials. For this application MSC must be ex-vivo expanded in order to obtain, for a given volume of implanted biomaterial, a relevant number of bone forming cells. Previously conducted pre-clinical studies suggested that a concentration of 6 x 10 8 ASC associated with 900 mg of anorganic bovine bone (ABB) could be effective for human maxillary sinus floor elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…For one, the literature has shown that excessive adiposity has been associated with increased incidence of breast cancer in postmenopausal women, likely due to IL-6 secretion by ASC which is hypothesized to promote migration and invasion of breast cancer cells [87,88] . Another study performed ex vivo detected chromosomal abnormalities after extended ASC expansion in culture [89] , similar to the findings of other groups that culture propagation of MSC introduces genetic instability and tumorigenicity [90] . Furthermore, one ASC study pertaining to bone formation in canine by Kang et al found cytologic abnormalities along with increased proliferation associated with ASC [91,92] .…”
Section: Discussionsupporting
confidence: 83%
“…For one, the literature has shown that excessive adiposity has been associated with increased incidence of breast cancer in postmenopausal women, likely due to IL-6 secretion by ASC which is hypothesized to promote migration and invasion of breast cancer cells [87,88] . Another study performed ex vivo detected chromosomal abnormalities after extended ASC expansion in culture [89] , similar to the findings of other groups that culture propagation of MSC introduces genetic instability and tumorigenicity [90] . Furthermore, one ASC study pertaining to bone formation in canine by Kang et al found cytologic abnormalities along with increased proliferation associated with ASC [91,92] .…”
Section: Discussionsupporting
confidence: 83%
“…; Bellotti et al. ). To our knowledge, karyotype stability has not been studied extensively in dog AdMS cells, but published studies to date suggest that, like human AdMS cells, dog cells have a stable karyotype (Vieira et al.…”
Section: Discussionmentioning
confidence: 97%
“…The AdMS cells used to generate the canine iPSCs had an abnormal karyotype, displaying both aneuploidy and the appearance of metacentric chromosomes at low passage (P5). Human AdMS cells have been shown to exhibit karyotype abnormalities but only following prolonged culture periods (Izadpanah et al 2008;Bellotti et al 2013). To our knowledge, karyotype stability has not been studied extensively in dog AdMS cells, but published studies to date suggest that, like human AdMS cells, dog cells have a stable karyotype (Vieira et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other obstacles that must be addressed include the need for development of suitable serum free media for these cells as fetal bovine serum (FBS) is not recommended for clinical therapies given the risk of contamination and infection. Current strategies require ex vivo expansion of cells for two or three weeks rendering them susceptible to the possibility of genomic instability in culture [98]. Attempts at designing devices that enable a single step harvest, manipulation and grafting are therefore needed and would obviate the need for cell culture and the attendant risks of using FBS [99,100].…”
Section: Clinical Applicationsmentioning
confidence: 99%